Question

By using u=ln(3x) and dv=6x dx, find ∫ 6x ln(3x) dx. Be sure to include the argument of the logarithm in parentheses.

Step 1

Consider the integral

Step 2

The formula for integration by parts is given as

Step 3

Substitute *u *= ln(3*x*) and d*v *= *6x* d*x* in the formula for ...

Tagged in

Q: 13. A 13 foot sliding ladder is leaning against a house when its base starts to slide away. By the t...

A: We are given diagram as

Q: Please help me about this.

A: The radius of convergence is 4 which can be computed as follows.

Q: I got up to: 60-62t, then started doing 30 + the integral from t to 0 but I don’t know if I’m doi...

A: To find velocity we have to integrate a(t)= -62Answer: Velocity: v(t)=-62t+60

Q: If y' 6x - 3 and y(2) 6 4, then y 3x2- 3x 3x2-3x-2 3x2-3x2 6x2-3x2

A: Given:

Q: Let R be the region bounded by the following curves. Use the shell method to find the volume of the ...

A: Consider the provided curve:

Q: Calculate S3, S, and S5 and then find the sum for the telescoping series 410 n3n1 n +2 n-3 where Sk ...

A: to determine the first few partial sums and the sum to infinity of the given telescoping series

Q: find the volume aquired by taking by region bound by y=x^2 and y=x^4 and rotating it around x=-1

A: To calculate the volume bounded by the curve y=x2 and y=x4 which is rotating about the line x=-1. No...

Q: Determine the radius of convergence of the following power series. Then test the endpoints to determ...

A: We have been given a power series and we are required to find its radius of convergence as well as i...

Q: x1 J: (x2+2x)2 dx= (x2+2x)3 C (x2 2x)3 C + 3 (x2+2x)3 +C 6 22-1C + -2 2x)1+C

A: Click to see the answer

Sorry about that. What wasn’t helpful?